Exploring Multi-level Parallelism in Atmospheric Applications - Schepke, Claudio; Maillard, Nicolas (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2012: Anais do XIII Simpósio em Sistemas Computacionais de Alto Desempenho, 2012)
Forecast precisions of climatological models are limited by computing power and time available for the executions. The more and faster processors are used in the computation, the resolution of the mesh adopted to represent the Earth's atmosphere can be increased, and consequently the numerical forecasts are more accurate. With the introduction of multi-core processors and GPU boards, computer architectures have many parallel layers. Today, there are parallelism inside a processor, among processors and among computers. In order to best utilize the performance of the computers it is necessary to consider all parallel levels to distribute a concurrent application. However, no parallel programming interface abstracts well these different parallel levels. Based in this context, this work proposes the use of mixed programming interfaces to improve performance to atmospheric models. The parallel execution of simulations shows that the use of GPUs and multi-core CPUs in distributed systems can reduce considerably the execution time of climatological applications.